Aloe-derived vesicles enable macrophage reprogramming to regulate the inflammatory immune environment - Zhou, Hao; Peng, Ke; Wang, Jun; Wang, Yang; Wang, Jia-Jia; Sun, Shi-Kun; Shi, Mai-Qing; Chen, Jun; Ji, Fu-Hai; Wang, Xu (Frontiers in Bioengineering and Biotechnology, 2023)
Bacterial pneumonia poses a significant global public health challenge, where unaddressed pathogens and inflammation can exacerbate acute lung injury and prompt cytokine storms, increasing mortality rates. Alveolar macrophages are pivotal in preserving lung equilibrium.Excessive inflammation can trigger necrosis in these cells, disrupting the delicate interplay between inflammation and tissue repair. In our study, we discovered the potential of extracellular vesicle nanovesicles derived from aloe in reprograming macrophage phenotypes.Pro-inflammatory macrophages undergo a transition towards an anti-inflammatory immune phenotype through phagocytosing and internalizing these aloe vera-derived extracellular vesicle nanovesicles. This transition results in the release of anti-inflammatory IL-10, effectively curbing inflammation and fostering lung tissue repair. These findings firmly establish the immunomodulatory impact of aloe-derived extracellular vesicle nanovesicles on macrophages, proposing their potential as a therapeutic strategy to modulate macrophage immunity in bacterial pneumonia.